2004
DOI: 10.1161/01.atv.0000133604.20182.cf
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Protection

Abstract: Abstract-Blood vessels express 3 isoforms of superoxide dismutase (SOD): cytosolic or copper-zinc SOD (CuZn-SOD), manganese SOD (Mn-SOD) localized in mitochondria, and an extracellular form of CuZn-SOD (EC-SOD). Because there are no selective pharmacological inhibitors of individual SOD isoforms, the functional importance of the different SODs has been difficult to define. Recent molecular approaches, primarily the use of genetically-altered mice and viral-mediated gene transfer, have allowed investigators to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(213 citation statements)
references
References 109 publications
4
208
1
Order By: Relevance
“…SOD is the primary scavenger of O 2 ·-in endothelial cells, through a reduction of two O 2 ·-molecules resulting in H 2 O 2 and O 2 (Griendling et al 2000a;Salvemini et al 2002). The total percentage of each SOD isoform expressed in different vascular cells was recently reviewed by Faraci et al (Faraci et al 2004). High levels of MnSOD were found in endothelial cells.…”
Section: Superoxide Dismutasementioning
confidence: 99%
See 2 more Smart Citations
“…SOD is the primary scavenger of O 2 ·-in endothelial cells, through a reduction of two O 2 ·-molecules resulting in H 2 O 2 and O 2 (Griendling et al 2000a;Salvemini et al 2002). The total percentage of each SOD isoform expressed in different vascular cells was recently reviewed by Faraci et al (Faraci et al 2004). High levels of MnSOD were found in endothelial cells.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…ONOO -is formed through the interaction of NO and O 2 ·- Wattanapitayakul et al 2000;Guzik et al 2002) and O 2 ·-are roughly equivalent (Faraci et al 2004). NO availability is reduced with elevated concentrations of O 2 ·-, through the formation of ONOO -.…”
Section: Peroxynitritementioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] On the other hand, as indices of antioxidant potential, intracellular levels of superoxide dismutase and glutathione peroxidase have mainly been measured. [8][9] However, these assay methods are complex and are not suitable for analysis of a large number of subjects. Recently, simpler methods for detecting reactive oxygen species (ROS) using derivatives of reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) were developed, and reports on studies using these methods have been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…$ p<0.05 versus 2-h after meal intake. Different letters: the differences between diets are statistically significant (p<0.05) (Faraci and Didion 2004;Mates et al 1999;Rahman et al 2005). Our results showed that the gene expression of the mitochondrial SOD isoform, SOD2, seems to be modulated by dietary fat rather than by the cytoplasmatic isoform SOD1.…”
Section: Discussionmentioning
confidence: 61%